Seeking the right to food : food activism in South Africa - Nkrumah, Bright (Cambridge University Press, 2021)
Exploring why South Africans rarely use activism to address food insecurity, this study of collective action and food security in South Africa, presented alongside historical and contemporary case studies, proposes ways to reclaim the power of collective action to address food scarcity.